Human Factors Research and Design Trends for the Modern Exam and Hospital Room. (September 2015) - Saleem, Jason J.; Militello, Laura G.; Montague, Enid; Trbovich, Patricia; Russ, Alissa L.; Patterson, Emily S.
Although much research has been conducted on the impact of the electronic health record (EHR) and health information technology (HIT) on provider-patient interaction, challenges persist on how to effectively integrate these tools into healthcare environments, while maintaining patient-centered care. Panelists will present and discuss their experience relating to: the introduction of new technology and how it changes the nature of work; the positive impact of greater focus on the patient; the nature of interruptions and strategies to reduce their negative impact; enhancing the workflow of medication ordering; and designing collaborative spaces considering all relevant stakeholders (patient care team, patients, family members). These topics represent some of the latest human factors research and design trends with a common goal: advancing the design of the modern healthcare environment, with consideration of the additional complexity introduced by evolutionary changes in clinical information systems and HIT.